Improving Weed Control in Landscape Planting Beds - Chris Marble; Andrew Koeser (EDIS)
Because landscape beds often contain a variety of ornamental plants, shrubs, and trees, using herbicides to control weeds in these areas can be challenging; however, non-herbicidal methods can be labor intensive. This 6-page fact sheet outlines how to use landscape design and cultural and chemical practices to effectively control weeds in landscape beds. This publication also discusses the use of pre- and postemergent herbicides. Written by Chris Marble and Andrew Koeser, and published by the UF Department of Environmental Horticulture, June 2015.